Perancangan Website Dengan Usability Pada Toko Cek Hijab Baturaja Kabupaten Ogan Komering Ulu - Faulina, Sri Tita; Wisnumurti, Wisnumurti (TIN: Terapan Informatika Nusantara, 2020)
Computer technology today is a means of communication that brings a lot of change to the world of education, business, government agencies, and private sector. One form of technological development that is currently trending is website. Website is one of the applications on the internet in the form of Hypertext information, where Hypertext can read and browse the information virtually without being related to certain media. With the website is expected to help market products or services, promote a company, and others online. This website application helps users, in this case business owners both goods and services and internet connoisseurs in this case are consumers which with the existence of the website will cause a sense of comfort and provide convenience to the komsumen to be able to choose the goods according to the wishes. With an attractive look, and easy to understand website is expected to help business owners in increasing sales. Based on this thought, a website is created using the Usability method with the results in the form of an attractive website appearance for consumers.